PENGEMBANGAN POTENSI PARIWISATA, EKONOMI LOKAL BERBASIS E-COMMERCE KAWASAN WISATA GUNUNG IJEN KAB. BANYUWANGI - Ardianti, Riski Isminar (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2016)
The era of globalization make the move into tourism industry's largest and strongestin the financing of the global economy. The development of tourism has threefunctions Promote the economy; Maintaining the national identity and preservationof function and quality of the environment; foster a love for the homeland and thenation. Rapid technological advancesthat make more rapid dissemination ofinformation. The purpose of the study is to examine the promotion of e-commercecan increase the number of tourist visits in the tourist area ofMount Ijen andthrough the increase in traffic would improve the welfare of local communities. Thestudy population was a tourist visitor Mount Ijen by taking the sampling methodusing a random sampling of 350 samples, data collection techniques usingquestionnaires and interviews. Methods of qualitative and descriptive analysis usingbivariate analysis. The results of this study indicate that the tourism promotion Ijencrater through e-commerce can increase the number of tourist visits. Ijen cratertourism information through the Internet easier and cheaper to obtain travelinformation. With the increasing number of tourist visits Ijen crater memberspositive impact on the welfare of local communities, especially sulfur miners whowere around tourist sites Mount Ijen.